(untitled) (Research, Society and Development, 2021)
The objective of this study was to evaluate the effect of the increase in the level of CO2 in the environment on the growth of black pepper and common bean plants under competitive conditions. For this, an experiment was conducted in DIC with four repetitions. The effect of the black prick was evaluated in a 3 x 4 factorial scheme, with three concentrations of CO2 in the growth chambers (420; 840 and 1.680 µmol-1), and four arrangements: black prick cultivated alone, black prick + Brachiaria decumbens, picao-preto + corn and picao-preto + beans. For bean plants, the factorial scheme was 3 x 3, with the three levels of CO2 in the growth chamber mentioned and the different arrangements: beans cultivated in isolation, beans + picao-preto and beans + Brachiaria decumbens. Higher levels of CO2 promote the greatest gain in height and dry matter mass of the roots, stems and leaves of the crop and the weed. The total chlorophyll content was also higher at the highest levels of CO2 considering the two species evaluated. The increase in CO2 concentration affected the competition dynamics between the species evaluated. In the lowest concentration of ambient CO2, the bean proved to be more competitive with the black-pea plants in relation to the other species evaluated. In the concentrations of 840 and 1.680 µmol mol-1 of CO2, both corn and beans affected the growth of the black-pea plants. Bean plants were negatively affected by living with weeds at all levels of CO2 enrichment analyzed.